2004
DOI: 10.1111/j.1365-2761.2004.00558.x
|View full text |Cite
|
Sign up to set email alerts
|

The parasitic ciliate Ichthyophthirius multifiliis induces expression of immune relevant genes in rainbow trout, Oncorhynchus mykiss (Walbaum)

Abstract: During an infection with the parasitic ciliate Ichthyophthirius multifiliis, expression of genes encoding complement factor C3, inducible nitric oxide synthase (iNOS), immunoglobulin (IgM) and major histocompatibility complex (MHC-II) was examined in the skin, head kidney and spleen of rainbow trout using semi-quantitative reverse transcriptase-polymerase chain reaction. Induction of C3 transcription levels was evident in the skin and spleen showing extra-hepatic production of C3. MHC-II and IgM levels were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
74
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(89 citation statements)
references
References 33 publications
13
74
1
1
Order By: Relevance
“…Until recently there had been little direct evidence of innate immune mechanisms against parasites associated with mucosal epithelium [285]. The active immunological role of skin against parasitic infection has been shown recently [286][287][288], and now mucosal immunity against them start to be elucidated. The physicochemical characteristics of skin mucus, the presence of bioactive molecules (lysozyme, complement, C-reactive protein, haemolysins, and lectins) and epidermal migration of inflammatory cells and their secretion may affect the establishment and proliferation of parasites [289].…”
Section: Fish Skin Mucosal Immunologymentioning
confidence: 99%
See 1 more Smart Citation
“…Until recently there had been little direct evidence of innate immune mechanisms against parasites associated with mucosal epithelium [285]. The active immunological role of skin against parasitic infection has been shown recently [286][287][288], and now mucosal immunity against them start to be elucidated. The physicochemical characteristics of skin mucus, the presence of bioactive molecules (lysozyme, complement, C-reactive protein, haemolysins, and lectins) and epidermal migration of inflammatory cells and their secretion may affect the establishment and proliferation of parasites [289].…”
Section: Fish Skin Mucosal Immunologymentioning
confidence: 99%
“…The expression profiles of some cytokines and their receptors (IL-1β, IL-8, TNFα, and IL-1-Receptor 1) in the skin have also been examined in several fish species, and they are upregulated by infection of mechanical injury to the skin [288,[347][348][349]. IL-1b gene 1 is significantly expressed in many tissues (liver, head kidney, spleen, intestine, and muscle, but minimally in stomach, brain, and ovary) and skin of pufferfish.…”
Section: Genetic Studies In Fish Skinmentioning
confidence: 99%
“…Induction of adaptive immune responses to I. multifiliis has been observed within days following initial exposure. The earliest response correlated with infection is an increase in the level of total IgM mRNA, detected by reverse transcription-PCR, in skin or head kidney samples 4 d after infection of rainbow trout Onchorhynchus mykiss with I. multifiliis (Sigh et al 2004). In channel catfish, antibodies specific for I. multifiliis can be detected in serum within 7 to 12 d following infection and within 12 d in the skin , Xu et al 2004).…”
Section: Quantitative Tail Infection Of Channel Catfish Withmentioning
confidence: 99%
“…Thus, vaccination against I. multifiliis can be considered an alternative to chemical treatments to prevent mortality (2) in fish. A number of studies have indicated that whole-cell trophonts, theronts, and ciliary protein preparations or recombinant i-antigen proteins of this parasite are able to induce an acquired immune response in numerous fish species, including the channel catfish (Ictalurus punctatus), trout (Salmo gairdneri), and carp (Cyprinus carpio) (2)(3)(4)(5). Trophonts are commonly inactivated by using 1%-4% formalin (5) or freezing (5) and used for immunization at different doses (5).…”
Section: Introductionmentioning
confidence: 99%